Repetitive Transcranial Magnetic Stimulation: Is it an Effective Treatment for Cancer Pain? - Yanyuan Du; Yaoyuan Li; Jieqing Hu; Ruiying Fang; Yuming Liu; Liu Cai; Ying Song; Susu Ma; Jin Gao; Hanyue Zhang; Baihui Li; Hongtai Xiong; et al. (Pain and Therapy)
Abstract Cancer is a major public health issue, with an estimated 20 million new cases and 9.7 million cancer-related deaths worldwide in 2022. Approximately 44.5% of patients experience cancer pain, significantly impacting their quality of life and causing physical and psychological burdens. Repetitive transcranial magnetic stimulation (rTMS), a non-invasive neuromodulation technique, shows potential in managing cancer pain. This review summarizes current research on rTMS for cancer pain, focusing on pain directly caused by tumors, pain from cancer treatments, postoperative pain, and cancer-related symptoms. Additionally, rTMS shows promise in improving cancer-related fatigue, anxiety, depression, and cognitive dysfunction, which can indirectly reduce cancer pain. The analgesic mechanisms of rTMS include inhibiting nociceptive signal transmission in the spinal cord, modulating hemodynamic changes in brain regions, and promoting endogenous opioid release. High-frequency stimulation of the primary motor cortex (M1) has shown significant analgesic effects, improving patients' emotional and cognitive functions and overall quality of life. rTMS has a favorable safety profile, with most studies reporting no severe adverse events. In conclusion, rTMS holds substantial potential for cancer pain management, offering a non-invasive and multifaceted therapeutic approach. Continued research and clinical application are expected to establish rTMS as an essential component of comprehensive cancer pain treatment strategies, significantly enhancing the overall well-being of patients with cancer.